Influence of loading orientation on mechanical properties of spot welds. (15th June 2022) - Shojaee, M.; Tolton, C.; Midawi, A.R.H.; Butcher, C.; Ghassemi-Armaki, H.; Worswick, M.; Biro, E.
Highlights: Novel triangulation method utilized for instantaneous nugget center point tracking. Deviation of shear/tensile loads was experimentally quantified during KS-II tests. Accuracy of failure criterion increased by accounting for nugget orientation. Local displacement tracking reduced the influence of slippage on absorbed energy. Crack propagation into FZ can limit post-failure energy absorption capability. Abstract: The mechanical performance and failure characteristics of resistance spot welds from two grades of third-generation advanced high strength steels (3G-AHSS), designated 3G-980 and 3G-1180, to combined/mixed loading were investigated by conducting KS-II tests in eight different loading orientations. Due to inherent difficulty in gripping the high strength 3G-AHSS, a combination of coupon rotation, slippage, and deformation occurred especially at shear-dominated loading orientations. This study utilized a new fixture based on Arcan-apparatus coupled with digital image correlation technique to track the instantaneous orientation of the KS-II coupons. This way, the actual proportion of shear and tensile components of force applied to the nugget, instead of the nominal ratio at the beginning of the tests, could be quantified experimentally, which in turn improved the calibration accuracy of a spot weld strength-based failure criterion. A novel triangulation method was proposed to minimize the influence of coupon slippage and deformation at regions away from the nugget on calculated absorbed energy. The more precise absorbed energy calculation was achieved by changing the displacement reference point from the crosshead to a local measurement between coupon halves. Energy absorption capabilities of the spot welds were calculated by separately tracking the deformation of the nugget in the shear and tensile directions. It was observed that within the tensile-dominated loading orientations (45°–90°) pullout failures of 3G-980 spot welds exhibit much higher post-failure energy absorption capabilities than the RSW of 3G-1180. The propagation of the formed cracks into the fusion zone was found responsible for the relatively inferior energy absorption capability of 3G-1180 joints. Graphical abstract: Image, graphical abstract